Expression of Herpes Simplex Virus Thymidine Kinase/Ganciclovir by RNA Trans-Splicing Induces Selective Killing of HIV-Producing Cells - Carin K. Ingemarsdotter; Sushmita Poddar; Sarah Mercier; Volker Patzel; Andrew M.L. Lever (Elsevier, 2017)
Antiviral strategies targeting hijacked cellular processes are less easily evaded by the virus than viral targets. If selective for viral functions, they can have a high therapeutic index. We used RNA trans-splicing to deliver the herpes simplex virus thymidine kinase-ganciclovir (HSV-tk/GCV) cell suicide system into HIV-producing cells. Using an extensive in silico bioinformatics and RNA structural analysis approach, ten HIV RNA trans-splicing constructs were designed targeting eight different HIV splice donor or acceptor sites and were tested in cells expressing HIV. Trans-spliced mRNAs were identified in HIV-expressing cells using qRT-PCR with successful detection of fusion RNA transcripts between HIV RNA and the HSV-tk RNA transcripts from six of ten candidate RNA trans-splicing constructs. Conventional PCR and Sanger sequencing confirmed RNA trans-splicing junctions. Measuring cell viability in the presence or absence of GCV expression of HSV-tk by RNA trans-splicing led to selective killing of HIV-producing cells using either 3' exon replacement or 5' exon replacement in the presence of GCV. Five constructs targeting four HIV splice donor and acceptor sites, D4, A5, A7, and A8, involved in regulating the generation of multiple HIV RNA transcripts proved to be effective for trans-splicing mediated selective killing of HIV-infected cells, within which individual constructs targeting D4 and A8 were the most efficient.